Concomitant Minimally Invasive HVAD and Transapical Aortic Valve Implantation. Issue 2 (March 2015) - Schaefer, Andreas; Treede, Hendrik; Bernhardt, Alexander; Wagner, Florian M.; Reichenspurner, Hermann; Deuse, Tobias
<x xml:space="preserve">Abstract</x> Minimally invasive left ventricular assist device (LVAD) implantation with the HeartWare VAD (HVAD) has been reported lately as an alternative approach to median sternotomy due to its favorable results regarding sternal wound complications, mediastinitis, postoperative bleeding, and right ventricular failure (RVF). Relevant aortic regurgitation is a cardiac comorbidity that requires surgical repair at the time of LVAD implantation to reduce recirculation and ensure adequate forward flow. We herein report on a patient with severely reduced left ventricular function due to ischemic cardiomyopathy, moderate aortic regurgitation, and a reduced right ventricular function. We performed minimally invasive HVAD implantation with concomitant transapical transcatheter aortic valve replacement. We believe this hybrid procedure could potentially reduce the risk for post-LVAD RVF because it preserves the pericardial geometry and obviates the need for cardioplegic arrest.